The measure : a novel - Erlick, Nikki (William Morrow, an imprint of HarperCollinsPublishers, 2022)
When every person, all over the globe, receives a small wooden box bearing the same inscription and a single piece of string inside, the world is thrown into a collective frenzy, in this novel told through multiple perspectives that introduces an unforgettable cast of characters.